In vitro combination of antifungal agents against Malassezia pachydermatis. (19th June 2018) - Schlemmer, Karine B; de Jesus, Francielli P K; Loreto, Erico S; Farias, Julia B; Alves, Sydney H; Ferreiro, Laerte; Santurio, Janio M
Abstract: The yeast Malassezia pachydermatis is a common commensal and occasional opportunistic pathogen of theskin microbiota of animals and humans. In this study, the susceptibility of M. pachydermatis isolates to fluconazole (FLC), itraconazole (ITZ), ketoconazole (KTZ), clotrimazole (CLZ), and miconazole (MCZ) alone and in combination with terbinafine (TRB), nystatin (NYS), and caspofungin (CSP) was evaluated in vitro based on the M27-A3 technique and the checkerboard microdilution method using Sabouraud dextrose broth with 1% tween 80 (SDB). Based on the mean FICI values, the main synergies observed were combinations of ITZ+CSP and CLZ+CSP (55.17%). The most significant combinations deserve in vivo evaluations because might provide effective alternative treatments against M. pachydermatis due to their synergistic interactions.